Acute Toxicity Study of the Combination of Azadirachta indica A. Juss. and Gynura procumbens (Lour.) Merr. Leave Extracts - Nofran Putra Pratama; Kurnia Rahayu Purnomo Sari; Ririn Irma Marliana (Journal of Fundamental and Applied Pharmaceutical Science, 2021)
Azadirachta indica A.Juss. and Gynura procumbens (Merr.) are medicinal herbs widely used in traditional medicine. Recent research on the combination of these two plants showed aggressive antioxidant activity. The combination results can improve insulin and beta-cell morphology and can increase insulin expression. The variety of activities performed is the basis for conducting acute toxicity tests on the ethanol extract of Azadirachta Indica A. Juss. and Gynura procumbens (Lour.) Merr. to increase public confidence in its efficacy and ensure the safety of its use. The acute toxicity test on the ethanol extract of Azadirachta Indica A. Juss. and Gynura procumbens (Lour.) Merr. was carried out on female Wistar rats by following the 423 procedures of OECD (Organization for Economic Cooperation and Development) Guideline with five groups of experimental animals, namely normal treatment, aquadest solvent treatment and 0.5 Na-CMC 0.5%, a separate treatment of the ethanol extract of Azadirachta Indica A. Juss., a separate treatment of the ethanol extract of Gynura procumbens (Lour.) Merr., and combination treatment of the ethanol extract of Azadirachta Indica A. Juss. and leaves of Gynura procumbens (Lour.) Merr. Furthermore, it was proceeded by observing the liver of the experimental animals histopathologically. The acute toxicity test results utilizing the 423 procedures of the OECD did not confirm any death or signs of toxicity in the experimental animals, and histopathological observations did not show any major histopathological damage. Based on these results, according to Globally Harmonized Classification System (GHS), the combination of the ethanol extract of Azadirachta Indica A. Juss. and Gynura procumbens (Lour.) Merr. is included in the unclassified category 2,000 mg/kg BW.